Process dynamics and control techniques - Seborg, Dale E.; Edgar, Thomas F.; Mellichamp, Duncan A.; Doyle, F. J. (John Wiley & Sons, 2017)
This edition provides chemical engineers with process control techniques that are used in practice while offering detailed mathematical analysis. Numerous examples and simulations are used to illustrate key theoretical concepts. New exercises are integrated throughout several chapters to reinforce concepts.